INDUCED PHENOLOXIDASE PROFILES IN SILKWORM Bombyx mori (L.) UNDER BIOTIC STRESS - Priya S, Vishnu; P, Somasundaram (International Journal of Engineering Technologies and Management Research, 2020)
Phenol oxidase (PO) is one of the stress enzyme protein in living organism. The conversion of Pro-PO into an activation form of PO required a stress protein. In the present study has emerged with the novel finding of induced phenoloxidase was identified under bacterial endotoxin viz., Lipopolysaccharide (LPS) activity using silkworm Bombyx mori as an animal model. The PO enzyme plays an important role for insect survival during pathophysiological conditions. The enzyme activity was analyzed from ten different silkworm races with two phenolic substrates viz., L-Dopa and Dopamine by Native-PAGE. The bacterially induced PO was found in hemolymph and midgut of silkworm, PO3 were induced by LPS injection. In control PO1 & PO2 are non-bacterially induced protein having the molecular weight of 72 and 71. The results shown that there is no substrate specificity and similar functional activity was found in hemolymph and midgut under pathogenic condition. It was observed that bacterially inducible PO clearly differed from non-inducible PO (control). At final observation of induced isozymes of PO in the haemolymph and midgut system of tolerant silkworm races points out the existence of biochemical immunity against biotic stress of LPS. This is the first report to document the silkworm immunity under the LPS toxin in different silkworm races to identify the tolerant and susceptibility against a biotic stress.